Marriage following the 1997 Umbria-Marche (Italy) earthquake. Issue 1 (28th January 2014) - Prati, Gabriele; Pietrantoni, Luca
Abstract : Purpose: – The purpose of this paper is to replicate Cohan and Cole (2002) Hurricane Hugo study in the context of a different type of natural hazard and in a different country. Design/methodology/approach: – Change in marriage following the 1997 Umbria-Marche (Italy) earthquake was examined prospectively from 1987 to 2007 for the 15 municipalities declared disaster areas and for the whole Marche region and country. Findings: – Autoregressive integrated moving average time-series analysis showed that the year following the earthquake marriage rates decreased only in the 15 municipalities declared disaster areas. Originality/value: – In the present study, the paper found results in the opposite direction to Cohan and Cole (2002) Hurricane Hugo study. Taken together, the findings suggest that the direction of the change may be in either direction and depends on the characteristics of the disaster, of the response to it, and on social and economic conditions of the context.